Studies on parasitoids of the diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), in South Africa - Nofemela, Sicelo Robert (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2004)
The diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), is a major pest of Brassica crops in many parts of the world. Because of its ability to develop resistance to virtually all major groups of insecticides, including Bacillus thuringiensis Berliner (Bt), much attention has therefore been given to biological control using parasitoids. South Africa has an abundance of parasitoids attacking this pest. Cotesia plutellae (Kurdjumov) (Hymenoptera: Braconidae) is the most abundant larval parasitoid of P. xylostella in South Africa. In East Africa, its role in biological control of P. xylostella is insignificant, and the most abundant parasitoid there is Diadegma mollipla (Holmgren) (Hymenoptera: Ichneumonidae), a larvalpupal parasitoid. In South Africa, however, D. mollipla is out-competed by C. plutellae. Total parasitism of P. xylostella in East Africa rarely exceeds 15%, therefore there is a need to introduce more effective and heat-tolerant parasitoids of P. xylostella to that region. This study was therefore initiated to examine the potential of C. plutellae and D. mollipla as biological control agents by studying certain aspects of their biology in the laboratory, as well as the suitability of C. plutellae for introduction into East Africa. Biological aspects studied were: (i) host instar preference, fecundity, and searching efficiency of C. plutellae and D. mollipla at different host and parasitoid densities; (ii) effects of temperature on parasitism of P. xylostella by C. plutellae and D. mollipla, and on their rates of development and emergence. In addition, the role of parasitoids in controlling P. xylostella on unsprayed cabbage plots was investigated. Both C. plutellae and D. mollipla preferred to attack second and third instar hosts than fourth instars in choice and no-choice tests. However, D. mollipla attacked more fourth instar hosts than C. plutellae. Cotesia plutellae laid mainly female eggs in second and third instar hosts than in fourth instars, whereas D. mollipla laid more female eggs in fourth instar hosts than in second and third instar hosts. Diadegma mollipla was more fecund [82.57 ± 32.87, (mean ± s.d.) than C. plutellae (42.13 ± 12.2), and was long lived (7.13 ± 3.69 days) compared to the latter (5.23 ± 2.7 days). An increase in host density resulted in the reduction in the area of discovery (a) and the killing power (K) for both parasitoids. No significant differences were detected between the searching efficiency (t = -1.42NS, d.f. = 48, P < 0.001) of the two parasitoids. An increase in parasitoid density also resulted in a decline in searching efficiency, but not the killing power, of both parasitoids. Cotesia plutellae completed development at all temperatures tested (21-33°C), whereas D. mollipla completed development at temperatures from 18-30°C, and C. plutellae had a lower threshold for development (8.14°C) compared to D. mollipla (10.23°C). At all tested temperatures, the generation time for C. plutellae was shorter compared to D. mollipla. The possible reasons for the dominance of C. plutellae over D. mollipla in the field are: shorter generation time, high production of female progeny in younger hosts, low interference among searching females, and relatively wide thermal tolerance. The role of parasitoids in regulating diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), populations was studied for two years (February 2000-January 2002) on unsprayed cabbage fields at Brits, North West Province, South Africa. Cabbage seedlings were transplanted in three consecutive times each year. Cabbage infestations by P. xylostella larvae and pupae, and their parasitoids, were monitored at weekly intervals. The flight activity of P. xylostella male moths was monitored using sex-pheromone traps. Trap catches indicated that the moths were active throughout the year. The flight activity of the moths corresponded with infestations on the crop. Trap catches and infestation levels were generally low from December to August and high from September to November. Eight hymenopteran parasitoids were reared: the larval parasitoids Cotesia plutellae (Kurdjumov) (Braconidae) and Apanteles halfordi (Ullyett) (Braconidae); the larval-pupal parasitoids Oomyzus sokolowskii (Kurdjumov) (Eulophidae) and Diadegma mollipla (Holmgren)(Ichneumonidae); the pupal parasitoid Diadromus collaris (Gravenhorst) (Ichneumonidae); and the hyperparasitoids Eurytoma sp. (Eurytomidae), Mesochorus sp. (Ichneumonidae), and Pteromalus sp. (Pteromalidae). Cotesia plutellae was the most abundant parasitoid of P. xylostella followed by O. sokolowskii, D. collaris, A. halfordi and D. mollipla. Parasitism of P. xylostella larvae was high reaching 100% on several occasions during late spring to end of autumn (November-May) each year. Parasitism was lower (<50%) in winter and early spring (June-September). Apanteles halfordi was absent in winter but re-appeared in spring. Parasitism of P. xylostella pupae by D. collaris was high only during spring (September-October). Hyperparasitism was generally low except when primary parasitoids were abundant in spring (September-November) and summer (December-February) when up to 25% of P. xylostella larvae and C. plutellae cocoons yielded hyperparasitoids. The role of other biotic and abiotic mortality factors on the population dynamics of P. xylostella is discussed.
Keywords: Plutellidae -- South Africa; Plutellidae -- Biological control; Plutellidae -- Parasites; Parasitoids